Demonstration of microfiber hybrid Mach–Zehnder and knot resonator structure. Issue 1 (20th November 2012) - Sulaiman, A.; Harun, S. W.; Ahmad, F.; Muhammad, M.Z.; Jasim, A. A.; Ahmad, H.
Abstract We demonstrate a microfiber hybrid structure consisting of a microfiber knot resonator (MKR) and a microfiber Mach–Zehnder interferometer (MMZI) by micro‐manipulating a microfiber. The microfiber used has a waist diameter of 1 μm and is fabricated using a flame brush technique. The hybrid structure generates dual resonances spectrum, which combines a characteristic resonant of MKR and MMZI. The MMZI resonant exhibits a much higher free spectral range (FSR) of 3.1 nm with the extinction ratio of 3 dB. The MKR resonant has a FSR of 0.24 nm and extinction ratio of 5 dB. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:100–102, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27250